Formation and structural characterization of silver nanoparticles in ormosil sol–gel films - Reisfeld, Renata; Saraidarov, Tsiala; Levchenko, Victoria (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Silver nanoparticles were obtained in situ in ormosil sol–gel films with attached urethane groups. Optical spectra of the silver nanoparticles in the films show red shift of absorption maximum with increasing silver concentration from 2% to 10%. In the solutions λmax is shifted from 390 nm till 425 nm; in the films λmax is shifted from 438 nm till 456 nm. Structural characterizations of the composite sol–gel films incorporated by silver nanocrystals have been studied by: scanning electron microscopy (SEM), atomic force microscope (AFM), energy dispersion X-rays analysis (EDAX), high resolution transmission electron microscopy (HRTEM), selected area electron diffraction (SAED) and scanning transmission electron microscopy (STEM). Two types of silver nanoparticles with sizes of 1–2 nm and 20–40 nm were observed. The crystal grow process and particle sizes depend on the starting concentrations of silver ions, reaction temperature and time. The small silver particles are arranged in micro pores of the matrix, as shown from STEM images. SAED confirms the silver face-centered cubic crystal lattice.
Optica Applicata, Vol. 38, 2008, nr 1, s. 83-92
Keywords: optyka; silver nanoparticles; ormosil sol–gel composite; optical and structural characterizations